Reading slowly: a Festschrift for Jens E. Braarvig - Edzard, Lutz; Borgland, Jens W.; Hüsken, Ute; Braarvig, Jens E. (Harrassowitz Verlag, 2018)
Cover; Titel; Imprint; Table of Contents; Acknowledgments; Laudatio; Silje Susanne Alvestad: O. Nova 546: The Uppsala Manuscript of ""Maḳbūl-i ʿārif"" (1631); Christoph Anderl: Metaphors of "Sickness and Remedy" in Early Chán Texts from Dūnhuáng; Øivind Andersen: Homer's Sirens; Stefan Baums: A New Gāndhārī Document from Niya; Amund Bjørsnøs: Jāhilliya and Rahbāniyya in the Qurʼān: A Philological Essay
Keywords: Festschrift; Bibliografie; Historische Sprachwissenschaft; Orientalische Sprachen; Braarvig, Jens E.